The Role of Islamic Work Ethics in Moderating Influence Love of Money and Machiavellian Nature to Fraud Accounting in Management of Village Funds - Parawansa, Khofifah Indar; Winarto, Wahid Wachyu Adi (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
The number of fraud cases in Indonesia has been increasing annually, and it has started to spread to the countryside. This turns into an irony as the hamlet continues to grow and evolve into a sophisticated community. The goal is to investigate how a love of money and other Machiavellian traits affect the tendency for fraud accounting when using village funds, as well as how the Islamic work ethic influences the interaction between the village apparatus and the community in Wonokerto District. The SEM-PLS technique is being used in this quantitative study. Primary data were employed, and 66 persons made up the sample size through the use of purposive sampling procedures in conjunction with the questionnaire method of data collecting. According to the findings, the inclination of accounting fraud was significantly influenced by both love of money and Machiavellian tendencies, and the Islamic work ethic was found to be ineffective in mitigating this effect.